2014
DOI: 10.1080/09593330.2014.893023
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vanadium toxicity at its different oxidation states on selected bacterial and protozoan isolates in wastewater systems

Abstract: This study assesses and compares vanadium toxicity in its different oxidation states towards bacterial isolates (Pseudomonas putida and Bacillus licheniformis) and protozoan isolates (Peranema sp. and Trachelophyllum sp.). The isolates were exposed to various concentrations of V in mixed liquors and their tolerance to V was assessed at 30 degrees C at a pH of 4. The results revealed that the increase in V oxidation state increased its toxicity to bacterial isolates, whereas its toxicity decreased for protozoan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 54 publications
(62 reference statements)
1
6
0
Order By: Relevance
“…The LC 50 values observed for the ciliated protozoa of Lake Maracaibo, in general, are relatively high and comparable to those of other water bodies (Maurya & Pandey, 2020;Kamika & Momba, 2014;Madoni & Romeo, 2006;Madoni et al, 1996). Madoni & Romeo (2006) reported toxic effects of 0.30, 0.89, 0.59 and 0.07 mgCd(II).L -1 , and of 110, 108, 0.1 and 0.1 mgCr(VI).L -1 for the ciliated protozoa Dexiotricha granulosa, Colpidium colpoda, Euplotes aediculatus and Halteria grandinella, respectively, showing great differences in tolerance, as observed in other species of ciliates.…”
Section: Toxicity Of Potentially Toxic Elements On Ciliated Protozoasupporting
confidence: 62%
See 1 more Smart Citation
“…The LC 50 values observed for the ciliated protozoa of Lake Maracaibo, in general, are relatively high and comparable to those of other water bodies (Maurya & Pandey, 2020;Kamika & Momba, 2014;Madoni & Romeo, 2006;Madoni et al, 1996). Madoni & Romeo (2006) reported toxic effects of 0.30, 0.89, 0.59 and 0.07 mgCd(II).L -1 , and of 110, 108, 0.1 and 0.1 mgCr(VI).L -1 for the ciliated protozoa Dexiotricha granulosa, Colpidium colpoda, Euplotes aediculatus and Halteria grandinella, respectively, showing great differences in tolerance, as observed in other species of ciliates.…”
Section: Toxicity Of Potentially Toxic Elements On Ciliated Protozoasupporting
confidence: 62%
“…Some examples of the acute toxicity of pentavalent vanadium on aquatic organisms are: Pseudomonas putida (bacteria) 180-200 mg.L -1 , Trachelophyllum sp. (protozoa) of 120-130 mg.L -1 (Kamika & Momba, 2014), D. magna (microcrustacean) of 1.2 mg.L -1 (Okamoto et al, 2015) and Salmo gairdneri (fish) of 2.0-13.2 mg.L -1 (Stendahl & Sprague, 1982). In the case of Lake Maracaibo, an ecotoxicity of V(V) for P. solida of 401.96 mg.L -1 has been documented; this bivalve has been proposed as a bioindicator for PTE in this ecosystem, due to its ability to incorporate, tolerate and bioaccumulate elements in higher concentrations and proportional to exposure levels (Rojas, 2012).…”
Section: Toxicity Of Potentially Toxic Elements On Ciliated Protozoamentioning
confidence: 99%
“…Studies have revealed that the possible toxic effects of V are related to its oxidation state, since this metal element can exhibit several oxidation states (À1 to +5). 102 Two of these oxidation states (V 4+ and V 5+ ) are considered to be predominant in the environment, and inhalation and ingestion are the main routes of absorption. From the perspective of practical application as smart coatings, as a type of common product within easy physical contact, the toxicity of materials needs to be of paramount concern in any investigation.…”
Section: Environmental Friendlinessmentioning
confidence: 99%
“…Vanadium oxyanions. Multiples studies have reported the reduction of V(V), V(IV) and V(III) to V(II) by multiple Pseudomonas (Lyalkova and Yurkova, 1991;Kamika and Momba, 2014) although the mechanisms by which these bioreactions occur have not been elucidated. Despite this, members of the Pseudomonas genus have shown great potential for effectively removing vanadate from polluted environments.…”
Section: àmentioning
confidence: 99%